Exit! A Prostitution Survivor Voice from South Africa. Issue 2 (December 2017) - Grootboom, Grizelda
The author shares her first-hand experience of sexual abuse and slavery on the streets of South Africa during and after apartheid. Reflecting on her days in prostitution, the author also provides an insight into how the prostituted woman is robbed off her dignity and how difficult it is to exit from the physical and mental trauma. She explains the meaning of freedom after apartheid for the street children of South Africa. They celebrated the end of the systemic marginalization of black people but continued to face rampant substance abuse, sexual violence and 'gangsterism'. This article is a testimony of her from sex slavery to a survivor leader and activist against the backfrop of the apathy of the South African state towards its vulnerable children.